The value of combined examination of serum serum heparin binding protein, tumor necrosis factor alpha, interleukin-6, platelet count, and c-reactive protein in evaluating the condition and prognosis of children with adenovirus pneumonia - Wang, Guangjun; Liu, Jibin; Yu, Xuejiao; Cao, Shuzhen (Frontiers in Pediatrics, 2025)
BackgroundAdenovirus pneumonia presents a significant challenge in pediatric care, with severe children leading to significant morbidity. The study evaluated the combined prognostic value of serum Heparin Binding Protein (HBP), Tumor Necrosis Factor-alpha (TNF-α), Interleukin-6 (IL-6), platelet count (PLT), and C-Reactive Protein (CRP) levels in assessing the condition and prognosis of children with adenovirus pneumonia.MethodsThis retrospective study analyzed children with adenoviral pneumonia at our hospital from March 2019 to December 2024. Serum levels of HBP, TNF-α, IL-6, PLT, and CRP were measured. Participants were divided into non-severe and severe groups, and further into good and poor prognosis groups, based on clinical criteria and complications. Statistical analyses compared biomarker levels across these groups and evaluated their prognostic accuracy using receiver operating characteristic (ROC) curve analysis.ResultsElevated serum levels of HBP, TNF-α, IL-6, and CRP were significantly associated with severe adenovirus pneumonia (P < 0.001) in 300 children. Lower PLT was noted in severe children (P < 0.001). The composite model exhibited a high predictive accuracy with an AUC of 0.945 for disease severity and 0.940 for prognosis.ConclusionThe combination of serum HBP, TNF-α, IL-6, PLT, and CRP effectively predicted disease severity and prognosis in pediatric adenovirus pneumonia.